Exploring the Impact of COVID-19 Lockdown on Social Roles and Emotions while Working from Home - Nolan, Sam W.; Rumi, Shakila Khan; Anderson, Christoph; David, Klaus; Salim, Flora D. (2020)
ABSTRACT In the opening months of 2020, COVID-19 changed the way for which people work, forcing more people to work from home. This research investigates the impact of COVID-19 on five researchers’ work and private roles, happiness, and mobile and desktop activity patterns. Desktop and smartphone application usage were gathered before and during COVID-19. Individuals’ roles and happiness were captured through experience sampling. Our analysis show that researchers tend to work more during COVID-19 resulting an imbalance of work and private roles. We also found that as working styles and patterns as well as individual behaviour changed, reported valence distribution was less varied in the later weeks of the pandemic when compared to the start. This shows a resilient adaptation to the disruption caused by the pandemic. Keywords behavior logs, productivity, working from home, COVID-19, future of work, affective computing, social roles ABOUT THE AUTHOR/S Sam Nolan School of Science, RMIT University s3723315@student.rmit.edu.au Sam Nolan is a 3rd year honours student at RMIT University, President of the RMIT Programming club and Treasurer of the RMIT CSIT Society. His interests include functional programming (Haskell), type systems, data science, build systems and information theory. Shakila Khan Rumi School of Science, RMIT University shakilakhan.rumi@rmit.edu.au Christoph Anderson University of Kassel anderson@uni-kassel.de Klaus David University of Kassel david@uni-kassel.de Flora D. Salim School of Science, RMIT University flora.salim@rmit.edu.au New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).